PODCAST SEBAGAI MEDIA PEMBELAJARAN KETERAMPILAN MENYIMAK CERITA DONGENG BAGI SISWA KELAS II SDN PASIRANGIN - Pratiwi, Tiara Putri; Yuniarti, Yeni; Rakhmayanti, Fully (Universitas Tanjungpura, 2022)
Listening skills are the most basic skills that must be possessed by students. The low listening skills of the second grade students of SDN Pasirangin on the material of fairy tales and the lack of use of media are the background of this study. The purposes of the research are (1) to find out the use of podcast media in learning to listen the fairy tales and (2) to find out the learning outcomes from the use of podcast media in learning to listen the fairy tales. Learning media is an important component in learning. Podcast media as an audio-digital based learning media is expected to improve students